Nonlinear Modelling of Economic Growth and Unemployment in South Africa: Array - Sere, Kebitsamang Annah; Tchereni, Betchani (Acta Universitatis Danubius. Œconomica, 2020)
This study investigated the non-linear relationship between economic growth and unemployment in South Africa using quarterly data spanning from 1994Q1 to 2019Q4 with Okun’s (1969) law serving as the foundation of the study. Prior studies conducted in South Africa using different methodologies have produced mixed results. Some studies have proven evidence of Okun’s law whilst others have not. Using Nonlinear Autoregressive Distributive Lag approach proposed by Shin, Yu and Greenwood-Nimmo (2013) the findings suggest that although unemployment does not explain the changes in economic growth, it affects it positively. This implies that investment in capital intensive production increases unemployment between 1 and 20 percentage points. However, in the short run both positive and negative unemployment are negative and significant suggesting that when unemployment decreases, economic growth increases. These key findings are consistent with Okun’s law (1969). Therefore, the South African government and policy makers need to apply expansionary policies that will lead to the stimulation of higher and increased economic growth whilst reducing unemployment. It is evident that the use of capital-intensive methods in the long run results in jobless growth but in short run job creation results in a decrease in unemployment and the economy produces at the level of full employment.